Fundamentals of roller integrated compaction control for oscillatory rollers and comparison with conventional testing methods. (15th December 2018) - Pistrol, Johannes; Adam, Dietmar
Abstract: Oscillatory rollers are used for compaction work in sensitive areas like inner city construction sites or near vibration-sensitive structures due to their ability to cause very low ambient vibrations. The fundamentals of oscillatory roller compaction and Continuous Compaction Control (CCC) with oscillatory rollers are discussed within the present paper. The influence of the soil stiffness on the motion behaviour of an oscillatory drum was studied to introduce a novel CCC value for oscillatory rollers based on these findings. The algorithm for the calculation of this novel CCC value for oscillatory rollers is tested on real acceleration measurements obtained from experimental field tests. Moreover, the CCC value is extensively compared to the results of dynamic load plate test by means of the Light Falling Weight Device and to the results of CCC measurements with vibratory rollers.